Human Subjects Research Guidelines for Undergraduate Researchers: An Analysis of Institutional Review Board (IRB) Websites at Top Liberal Arts Colleges in the United States - Marcos Miguel, Nausica; Noy, Shiri (Journal of empirical research on human research ethics, 2023)
Teaching students about the ethics of Human Subject Research (HSR) should be a fundamental component of students’ education about research. In this article, we analyze the Institutional Review Board (IRB) websites of top-ranked Liberal Arts Colleges (LACs) to examine their framing of HSR carried out by undergraduate students. Our descriptive quantitative analysis from 50 top-ranked LACs in the United States indicates that a majority of IRB websites provide information about undergraduate research, and most include information about students’ classroom-based research. Our qualitative content analysis of a subsample of ten colleges’ IRB websites provides information on how they inform and educate about issues including informed consent and highlight different resources for students including their research advisor, and disciplinary standards. We conclude by discussing recommendations for IRBs in their accessibility to undergraduates.